Étude de la pyrroline déshydrogénase et de la régulation du catabolisme de l'arginine et de la proline chez Bacillus subtilis - De Hauwer, G.; Lavalle, R.; Wiame, J.M. (Biochimica et biophysica acta. Specialized section on enzymological subjects, 1964)
Two different enzymes which catalyze the same reaction may be induced in Bacillus subtilis. This reaction is the oxidation of Δ 1-pyrroline-5-carboxylic acid in glumatic acid. The difference between the two enzymes is shown by the study: (1) of their thermostability, (2) of their chromatographic behaviour on columns of DEAE-cellulose, (3) of their kinetic characteristics. The results obtained from mutants and the induction phenomenon are interpreted according to the ideas of Jacob and Monod on enzymic regulation. The present paper also completes the results concerning the characteristics of the two inductible enzymes. On peut induire, chez Bacillus subtilis, deux enzymes différents qui catalysent la même réation. Cette réaction est l'oxydation de l'acide Δ 1-pyrroline-5-carboxylique en acide glutamique. La différence entre les deux enzymes est montrée par l'étude: (a) de leur dénaturation thermique, (b) de leur comportement sur résine échangeuse d'ions, (c) de leurs caractéristiques cinétiques. Les résultats obtenus à partir de mutants et concernant le phénomène d'induction sont interprétés suivant les conceptions de Jacob et Monod sur la régulation enzymatique. Le présent travail complète aussi les données concernant les propriétés des deux enzymes inductibles.